ORGANIZATIONAL REWARD POLICY AND EMPLOYEE PRODUCTIVITY IN ANAMBRA STATE CIVIL SERVICE (2014 - 2020) (Journal of the Management Sciences, 2024)
A significant population of employees of Anambra state Government are demoralized which partly accounts for high absenteeism, lateness to work, low commitment which thereby dwindle their productivity due to fact that they are unfairly rewarded. This prompted the study to investigate the organizational reward policy and employee productivity: A study of Anambra state civil service (2014-2020). The study was guided by three objectives, three research questions and three hypotheses which were tested at 0.05 level of significance. Survey research design was employed for the study. The population of the study comprises 6,955 employees in Anambra State Civil Service. Morgan’s sample size determination table was adopted to draw 361 civil servants for the study. The sources of data collection were mainly through primary and secondary sources. Data collected were analyzed using frequency, percentages, mean, standard deviation and t-test. The study anchored on ‘Expectancy Theory’ as a framework for analysis. The findings of the study revealed among others that performance recognition has positive impact on the quality of employee output in Anambra State Civil Service. It was also found out that welfare scheme has significant impact on employee job satisfaction in Anambra State Civil Service. Based on the findings, it was recommended among others that the State Government should organize annual workshop and seminars for employees of Anambra state civil service to enrich them with knowledge and skills for improving their job performance.
Keywords: Organizational reward, policy, employee, productivity, civil service, Anambra State.